Increased Susceptibility to Cerebral Microhemorrhages Is Associated With Imaging Signs of Microvascular Degeneration in the Retina in an Insulin-Like Growth Factor 1 Deficient Mouse Model of Accelerated Aging - Miller, Lauren R.; Tarantini, Stefano; Nyúl-Tóth, Ádám; Johnston, Morgan P.; Martin, Teryn; Bullen, Elizabeth C.; Bickel, Marisa A.; Sonntag, William E.; Yabluchanskiy, Andriy; Csiszar, Anna; Ungvari, Zoltan I.; Elliott, Michael H.; et al. (Frontiers in Aging Neuroscience, 2022)
Age-related cerebrovascular defects contribute to vascular cognitive impairment and dementia (VCID) as well as other forms of dementia. There has been great interest in developing biomarkers and other tools for studying cerebrovascular disease using more easily accessible tissues outside the brain such as the retina. Decreased circulating IGF-1 levels in aging are thought to contribute to the development of cerebrovascular impairment, a hypothesis that has been supported by the use of IGF-1 deficient animal models. Here we evaluate vascular and other retinal phenotypes in animals with circulating IGF-1 deficiency and ask whether the retina mimics common age-related vascular changes in the brain such as the development of microhemorrhages. Using a hypertension-induced model, we confirm that IGF-1 deficient mice exhibited worsened microhemorrhages than controls. The retinas of IGF-1 deficient animals do not exhibit microhemorrhages but do exhibit signs of vascular damage and retinal stress such as patterns of vascular constriction and Müller cell activation. These signs of retinal stress are not accompanied by retinal degeneration or impaired neuronal function. These data suggest that the role of IGF-1 in the retina is complex, and while IGF-1 deficiency leads to vascular defects in both the brain and the retina, not all brain pathologies are evident in the retina.